Exotic fish and decreasing habitats vis-à-vis conservation of freshwater fish biodiversity of Bangladesh - Md. Abdul Gofur Khan; Shams M. Galib; Mahabuba Hasnath; Md. Rubel Mia; Raihan Kibria (Journal of Fisheries, 2022)
Multiple stressors including biological invasion have long been recognised in conservation of freshwater fish biodiversity. Works in this line have, however, been still scanty in Asia and South America – the continents known for rich biodiversity. In this study, the first of its type in Bangladesh, impacts of exotic fish and declining habitats on native fishes have been investigated. Regression and correlation analyses of 16 years production data of ponds, practically the only habitat where exotic fish are cultured commonly with indigenous ones, reveals that a maximum of 25% of the abundance decrease of native fish could be due to the effects of five commonly cultured exotic fish. Rest of the decline might largely be due to shrinkage, degradation, and destruction of habitats. Inland habitats other than ponds shrink, commonly, by about 80 % during the dry season, and most rivers are heavily polluted except for the brief mid rainy season. Decline in native fish populations may result in reduced genetic diversity. Another potential danger is the probable genetic introgression from the less fit hatchery-originated fish with the wild ones. The study concludes that the native freshwater fishes are endangered by declining habitats, exotic fishes, genetic consequences of hatchery supplementation